Longitudinal analysis of quality of life following treatment with Asunercept plus reirradiation versus reirradiation in progressive glioblastoma patients - Wick, Wolfgang; Krendyukov, Andriy; Junge, Klaus; Höger, Thomas; Fricke, Harald (Journal of neuro-oncology, 2019)
PurposeGlioblastoma is an aggressive malignant cancer of the central nervous system, with disease progression associated with deterioration of neurocognitive function and quality of life (QoL). As such, maintenance of QoL is an important treatment goal. This analysis presents time to deterioration (TtD) of QoL in patients with recurrent glioblastoma receiving Asunercept plus reirradiation (rRT) or rRT alone.MethodsData from patients with a baseline and ≥ 1 post-baseline QoL assessment were included in this analysis. TtD was defined as the time from randomisation to the first deterioration in the EORTC QLQ-C15, PAL EORTC QLQ-BN20 and Medical Research Council (MRC)-Neurological status. Deterioration was defined as a decrease of ≥ 10 points from baseline in the QLQ-C15 PAL overall QoL and functioning scales, an increase of ≥ 10 points from baseline in the QLQ-C15 PAL fatigue scale and the QLQ-BN20 total sum of score, and a rating of “Worse” in the MRC-Neurological status. Patients without a deterioration were censored at the last QoL assessment. Kaplan-Meier estimates were used to describe TtD and treatment groups (Asunercept + rRT or rRT alone) were compared using the log-rank test.ResultsTreatment with Asunercept + rRT was associated with significant improvement of TtD compared with rRT alone for QLQ-CL15 PAL overall QoL and physical functioning, and MRC Neurological Status (p ≤ 0.05). In the Asunercept + rRT group, QoL was maintained beyond progresison of disease (PoD).ConclusionTreatment with Asunercept plus rRT significantly prolongs TtD and maintains QoL versus rRT alone in recurrent glioblastoma patients.